2016
DOI: 10.1136/bmjresp-2016-000155
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestations and outcomes of pulmonary aspergillosis: experience from Pakistan

Abstract: IntroductionPulmonary aspergillosis has variable course of illness, severity and outcomes depending on underlying conditions. There is limited data available on the clinical manifestations and outcome of pulmonary aspergillosis from Pakistan.MethodsTo determine the clinical manifestations and outcome of pulmonary aspergillosis in a tertiary care hospital a retrospective study was conducted from 2004 to 2014 in patients admitted with pulmonary aspergillosis at the Aga Khan University Hospital Karachi, Pakistan.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
28
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 28 publications
8
28
1
1
Order By: Relevance
“…Underlying comorbidities may affect the outcome of patients with IA. Previous studies have demonstrated that bone marrow transplantation, diabetes and neutropenia are associated with an increased risk of mortality [ 1 , 16 , 19 ]. In the present study, bone marrow transplantation was the only comorbidity found to be predictive of mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Underlying comorbidities may affect the outcome of patients with IA. Previous studies have demonstrated that bone marrow transplantation, diabetes and neutropenia are associated with an increased risk of mortality [ 1 , 16 , 19 ]. In the present study, bone marrow transplantation was the only comorbidity found to be predictive of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have been inconsistent in identifying prognostic factors. A single center study of IA by Hsiue et al reported that steroid use correlated with poorer survival [ 15 ], while Iqbal et al found no significant association between steroid exposure and morality in Pakistani patients with IPA [ 16 ]. The latter authors identified respiratory failure, DM, and longer length of hospital stay to be independent factors that predicted poor outcome.…”
Section: Introductionmentioning
confidence: 99%
“…The number of patients registered with AKUH and diagnosed with aspergillosis (according to ICD-09), in 2015, were 49 (21) . Hence, using this population, one hundred and fourteen non-duplicate Aspergillus isolates were sampled to detect a hypothesized frequency of triazole resistance of 1.7 + 1% at 95% level of confidence.…”
Section: Interpretation Of Results: Breakpoints For Mold Testing Havementioning
confidence: 99%
“…The number of patients registered with AKUH and diagnosed with aspergillosis (according to ICD-09), in 2015, were 49 (22) . Hence, using this population, one hundred and fourteen non-duplicate Aspergillus isolates were sampled to detect a hypothesized frequency of triazole resistance of 1.7+1% at 95% level of confidence.…”
Section: Sample Sizementioning
confidence: 99%